2010
DOI: 10.7202/039827ar
|View full text |Cite
|
Sign up to set email alerts
|

Pratiques langagières et discours sur les langues et l’identité dans une entreprise montréalaise : contradictions et ajustements

Abstract: Ce texte examine les pratiques langagières et les discours sur la langue et l’identité dans une entreprise montréalaise de postproduction en pleine expansion. Les données nous révèlent un milieu où le français domine, mais où des stratégies sont mises en place pour gérer la communication bilingue ou multilingue. Malgré cette zone tampon (buffer zone), il devient apparent que le bilinguisme est une réalité pour la majorité des employés, même s’ils utilisent l’anglais de façon ponctuelle. De plus, nous constaton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 2 publications
1
14
0
1
Order By: Relevance
“…One is to work with higher frequency (e.g., in the Planck satellite, which observes, e.g., at 217, 353, 545 and 857 GHz) where the relative importance of grain emission increases with ν 2 , as anticipated in the Rayleigh-Jeans region, while the CMB is in the Wien region beyond 150 GHz. Repeating similar calculations, we have confirmed that the CMB anisotropy limit goes beyond what is expected from the extrapolation of the KBO observations with the canonical power of q = 3.5 if the 353 GHz observation with the Planck satellite (Lamarre et al 2010) would not see any signals beyond the cosmic variance.…”
Section: Discussionsupporting
confidence: 82%
“…One is to work with higher frequency (e.g., in the Planck satellite, which observes, e.g., at 217, 353, 545 and 857 GHz) where the relative importance of grain emission increases with ν 2 , as anticipated in the Rayleigh-Jeans region, while the CMB is in the Wien region beyond 150 GHz. Repeating similar calculations, we have confirmed that the CMB anisotropy limit goes beyond what is expected from the extrapolation of the KBO observations with the canonical power of q = 3.5 if the 353 GHz observation with the Planck satellite (Lamarre et al 2010) would not see any signals beyond the cosmic variance.…”
Section: Discussionsupporting
confidence: 82%
“…The contribution from patchy τ is shown in red, for a reionization model with z = 10, τ RMS = 0.0027. specifications, we expect the ACTPol and SPTPol experiments to be more sensitive to patchy kSZ, although it will still be very challenging to measure patchy τ using the CMB power spectra. We do not expect a significant improvement from the Planck mission, owing to the large (∼ 5 -7') beam width (Lamarre et al 2010), which limits CMB measurements to scales l < 2000. In the next section, we will discuss a much improved technique for detecting patchy reionization.…”
Section: Secondary Anisotropies Due Tomentioning
confidence: 88%
“…Frequency dependent secondary effects may be reduced by observing the CMB at multiple frequencies. The Planck Satellite, expected to release data in early 2013 consists of a Low Frequency Instrument (LFI) (Mandolesi et al 2010) which observes the CMB at frequencies 30 GHz, 44 GHz, and 70 GHz, as well as a High Frequency Instrument (HFI) (Lamarre et al 2010) sensitive to frequencies 100 GHz, 143 GHz, 217 GHz, 353 GHz, 545 GHz, and 857 GHz. The beam width varies from 33 arc minutes at 30 GHz to 5 arc minutes at 857 GHz (Mandolesi et al 2010;Lamarre et al 2010).…”
Section: Secondary Anisotropies Due Tomentioning
confidence: 99%
See 1 more Smart Citation
“…Par contre, le linguicisme (langue et accent) à la base de la discrimination serait le même pour les francophones et pour les anglophones québécois. D'autres chercheurs comme Lamarre et Lamarre, Magnan et Magnan et Lamarre s'intéressent notamment à la construction des identités chez les jeunes anglophones en contexte pluraliste (Lamarre et Lamarre, 2009;Magnan, 2008;Magnan et Lamarre, 2013 diplômés, les auteurs concluent qu'en dépit du fait que le bilinguisme domine dans le domaine de la gestion, la connaissance de l'anglais n'est jamais présentée comme un critère officiel d'embauche par les employeurs. Qui plus est, l'utilisation du français et de l'anglais varie selon plusieurs critères dont la taille de l'entreprise, le secteur d'activité et le poste occupé au sein de l'entreprise.…”
Section: Revue De La Littératureunclassified